Direct and Residual Effect of Zinc and Boron on Productivity, Nutrient Uptake and Quality on Mustard (Brassica juncea) and Succeeding Maize (Zea mays) in Subtropical Inceptisols of Jammu - Dileep Kachroo; Rajeev Bharat, Sarabdeep Kour, Meenakshi Gupta (Journal of the Indian Society of Soil Science, 2017)
A field experiment was conducted at research farm of Division of Agronomy, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu to study the effect of levels of zinc (Zn) (5 and 10 kg ha-1) and boron (B) (1 and 2 kg ha-1) and their foliar application alone and in different combinations on productivity, nutrient uptake and quality of mustard (Brassica juncea) in mustard-maize cropping sequence during 2010-11 and 2011-12 in subtropical Inceptisols of Jammu region. Zinc and B levels alone and in different combinations were applied to mustard crop during 2010 and 2011 and their residual effect was studied in succeeding maize crop. Highest grain and stover yield of mustard crop was recorded with the combined application of 10 kg Zn + 2 kg B ha-1 along with recommended dose of NPK fertilizers (RDF) and was at par with application of RDF + 10 kg Zn + 1 kg B ha-1, RDF + 5 kg Zn + 1 kg B ha-1 and RDF + 5 kg Zn + 2 kg B ha-1 but was significantly superior over RDF and other treatments. Higher levels of Zn and B along with RDF also recorded higher growth and yield attributes at harvest viz., plant height, branches plant-1, siliquae plant-1, seeds siliquae-1 and test weight of mustard crop than recommended dose of fertilizers and other treatments. Nutrient uptake viz., Zn and B uptake by both seed and stover of mustard crop also increased with increasing levels of both these nutrients and was superior over RDF as well as RDF along with sole application of Zn or B and foliar application treatments. Oil content and protein content also followed the same increasing trend. However, residual effect of application of Zn and B on the grain and stover yields of succeeding maize crop was non-significant though the increase was up to 13.3 and 11.36 per cent for seed and stover yield, respectively over RDF. Zinc and B uptake by maize crop also showed an increasing trend but the increase was statistically non-significant.